2020
DOI: 10.1287/orsc.2019.1352
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Cultural Holes in Organizations: The Dynamic Structure of Social Networks and Organizational Vocabularies Within and Across Subunits

Abstract: The mechanisms by which social networks and organizational vocabularies combine jointly to affect communication patterns across organizational boundaries remain largely unexplored. In this paper, we examine the mutually constitutive relation between the network ties through which organizational members communicate with each other and the vocabularies that they use to describe their organization. We suggest that the dynamic structure of social networks and organizational vocabularies is contingent on the formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(17 citation statements)
references
References 124 publications
0
17
0
Order By: Relevance
“…However, it is rare in the management literature to find analyses that treat communication as anything other than the expression, transmission, or representation of pre-existing information. Communication, in management studies' typical rendering, occurs inside or between (putatively pre-existing) organizations, as in the many studies of communication networks that locate communicating systems inside organizations rather than framing them as constituting that which we consider 6 to be organization (Nisar, Prabhakar & Strakova, 2019;Tasselli, Zappa & Lomi, 2020). A similar view crops up in the internal coordination literature, when communication is understood as capable of producing moments of coordinated activity, but not as generating the structures, roles, and routines 'inside' of which coordination occurs (Bruns, 2013;Im, Yates, & Orlikowski, 2005;Okhuysen & Bechky, 2009).…”
Section: Theorizing Communication Differentlymentioning
confidence: 99%
“…However, it is rare in the management literature to find analyses that treat communication as anything other than the expression, transmission, or representation of pre-existing information. Communication, in management studies' typical rendering, occurs inside or between (putatively pre-existing) organizations, as in the many studies of communication networks that locate communicating systems inside organizations rather than framing them as constituting that which we consider 6 to be organization (Nisar, Prabhakar & Strakova, 2019;Tasselli, Zappa & Lomi, 2020). A similar view crops up in the internal coordination literature, when communication is understood as capable of producing moments of coordinated activity, but not as generating the structures, roles, and routines 'inside' of which coordination occurs (Bruns, 2013;Im, Yates, & Orlikowski, 2005;Okhuysen & Bechky, 2009).…”
Section: Theorizing Communication Differentlymentioning
confidence: 99%
“…In our framework, each level of network change has some degree of autonomy and stability, yet each level is linked to and dependent upon other levels. Studies of network change either seek to understand the social processes that would lead certain nodes to be connected and other nodes to be disconnected (e.g., Clough & Piezunka, 2020; Tasselli, Zappa, & Lomi, 2020), or they attempt to explain change in network structures over time (e.g., Hernandez & Shaver, 2019; Kleinbaum, 2018).…”
Section: Conceptualizing Network Dynamicsmentioning
confidence: 99%
“…They also found that co-located teachers (i.e., spatially similar) communicated more frequently and felt more emotionally attached. Tasselli et al (2020) found that cultural similarity, in terms of managers sharing similar individual vocabularies in describing their organization, facilitates the formation of communication ties between formal organizational boundaries, nurturing informal task-related ties across subunits over time.…”
Section: Drivers Of Network Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, unlike market and hierarchical networks that treat knowledge as an asset, horizontal industry networks treat it as an interaction, in which case the focus of network function shifts to the social interaction, dialectical negotiation and reciprocal exchanges (Dooley & Gubbins, 2019;Eapen & Krishnan, 2019). Secondly, from a structural perspective, these networks; (1) may not restrict access to join, (2) are neither sanctioned nor hierarchical, (3) are socially connected than organisationally, and (4) provide voluntary attendance or participation (Hacker, Bodendorf, & Lorenz, 2017;Tasselli, Zappa, & Lomi, 2020). Consequently, traditional management approaches to manage knowledge become limited and may become dysfunctional.…”
Section: Introductionmentioning
confidence: 99%